Inter-clustering as a network of knowledge and learning: Multiple case studies - Mário Franco; Lurdes Esteves (Journal of Innovation & Knowledge (JIK), 2020)
Despite inter-clustering being an important specific form of inter-organizational network, it has rarely been investigated. So, from an inter-organizational network perspective, this study aims to deepen knowledge about inter-cluster relationships as a way to share knowledge and learning in six clusters/cases in Portugal. These cases give some interesting insights into these issues. With interviews applied to the executive directors of the selected clusters, together with documentary analysis, the empirical evidence obtained lets us conclude that inter-clustering is seen as a network promoting the share of knowledge and learning among the actors involved, and allowing improvement in the activity carried out, the product or service provided, at both the firm and regional level. This study presents some contributions as regards identifying some categories/topics for the challenges of inter-clustering: (1) inter-clustering as the share of knowledge, (2) restrictions and benefits of inter-clustering, and (3) size of the inter-cluster network and future expectations. Moreover, we extend the existing literature on knowledge management, organizational learning and inter-clustering. Inter-clustering relations also offer also a new framework to analyze a network of knowledge and learning that has seldom been studied.
Keywords: 650; Cluster; Cooperation; Innovation; Inter-clustering; Knowledge; Learning; Network